Abstract 13808: Implementation of Cardiopulmonary Exercise Testing and Its Impact on 2-year Outcomes in Acute Coronary Syndrome From Mie ACS Registry - Murakami, Hiroaki; Fujimoto, Naoki; Takasaki, Akihiro; Kurita, Tairo; Hoshino, Kozo; Sawai, Toshiki; Kambara, Atsushi; Kitamura, Tetsuya; Ichikawa, Takehiko; Ito, Masaaki; Dohi, Kaoru (Circulation, 2020)
IntroductionCardiopulmonary exercise testing (CPET) determines intensity for exercise rehabilitation which may improve outcomes in patients with acute coronary syndrome (ACS). However, it is unclear how many patients are given exercise education based on CPET around hospital discharge. PurposesTo assess the implementation of CPET and to evaluate the impacts of clinical parameters including CPET variables on 2-year outcomes in ACS patients. MethodsWe enrolled 3146 ACS patients without hemodialysis (age, 68±12 yrs; 78% male) 30 days after onset using data from Mie ACS registry, a prospective and multicenter registry, between 2013 and 2017. We compared clinical characteristics in patients with and without CPET at hospital discharge. Prognostic factors including CPET variables during the 2-year follow-up were determined. ResultsForty percent of the hospitals had CPET equipment. Out of 3146, 431 patients (12%) underwent CPET and were given CPET-based exercise education. Implementation of CPET was associated with younger age, male, ST-elevation myocardial infraction, and higher peak creatine phosphokinase (p≤0.03). While, hospitalization length <7 days or >21 days was inversely associated with CPET. During the 2-year follow-up, 198 all-cause deaths (6%) and 103 heart failure (HF) hospitalization were observed. Multivariate Cox regression analysis demonstrated that age, male, hospitalization length >21 days, Killip ≥2, mechanical circulatory and/or ventilator support were positive predictors of all-cause death. While, CPET around hospital discharge (hazard ratio, 0.52; 95%CI, 0.27-0.99, p<0.05) and hemoglobin level were independent negative predictors of all-cause death. Although patients with CPET tended to have greater myocardial damage, they did not have increased rate of HF hospitalization or major adverse cardiovascular events (MACE). When analyzed only in patients with CPET, peak oxygen uptake was the only independent predictor for all-cause death. ConslusionsThe number of patients who underwent CPET at discharge was small in our registry. Although the rate of HF hospitalization and MACE were similar in patients with and without CPET, CPET and CPET-based exercise education did reduce all-cause mortality in ACS patients.